A clinico pathological study and management of benign enlargement of prostate - Mor, Ashish; Sharma, Surender Mohan; Mukherjee, Sujoy; Jindal, Rishi (International Surgery Journal, 2018)
Background: Benign prostatic hyperplasia (BPH) is the non-malignant enlargement of the prostate gland. Prolonged obstructions may eventually lead to acute urinary retention, recurrent urinary tract infection, hematuria, bladder calculi, and renal insufficiency. Methods: Hundred cases of benign enlargement of prostate were studied from November 2015 to 2016. Patients diagnosed as benign enlargement of prostate by clinical digital rectal examination, investigation like USG were included in this study. Patients with urinary retention due to strictures and urolithiasis, carcinoma were excluded. Results: Mean age of presentation was 64.4, and 34% were found to be in severe group of IPSS grading. There was a significant co-relation between the PVRU and prostate volume. There were 16% cases of acute urinary retention, 2% cases presented with bladder stones. Benign enlargement of prostate, IPSS score, Post voidal residual urine has a weak correlation with the increasing age as observed. Conclusions: Benign enlargement of prostate is a disease of elderly with peak incidence in the 5th and 6th decade of life, BPH has co-relation with inguinal hernia, AUR which is 16%. There was no correlation between the age of the patient and the severity of symptoms with respect to IPSS score. There was no correlation between the age of the patient and the severity of symptoms with respect to IPSS score. In present study there was a statistically significant relation were found between prostate volume and post voidal residual urine. Large amount of residual urine is the indication for surgery because it predisposes to infections and stone formation.